2020
DOI: 10.1101/2020.09.24.312058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human FcRn expression and Type I Interferon signaling control Echovirus 11 pathogenesis in mice

Abstract: Neonatal echovirus infections are characterized by severe hepatitis and neurological complications that can be fatal. Here, we show that expression of the human homologue of the neonatal Fc receptor (hFcRn), the primary receptor for echoviruses, and ablation of type I interferon (IFN) signaling are key host determinants involved in echovirus pathogenesis. We show that expression of hFcRn alone is insufficient to confer susceptibility to echovirus infections in mice. However, expression of hFcRn in mice deficie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 47 publications
3
4
0
Order By: Relevance
“…Consistent with our previous findings with E11 (21), we found that there was robust replication in the livers and pancreases of E5 infected hFcRn Tg32 -IFNAR -/mice (12 of 12 mice) (Supplemental Figure 1C, 1D). However, in contrast to the brain, we found that hFcRn Tg32 -IFNLR -/animals also contained virus in the liver (4 of 8 mice) and pancreas (8 of 8 mice) (Supplemental Figure 1C, 1D).…”
Section: Figure 1b)supporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with our previous findings with E11 (21), we found that there was robust replication in the livers and pancreases of E5 infected hFcRn Tg32 -IFNAR -/mice (12 of 12 mice) (Supplemental Figure 1C, 1D). However, in contrast to the brain, we found that hFcRn Tg32 -IFNLR -/animals also contained virus in the liver (4 of 8 mice) and pancreas (8 of 8 mice) (Supplemental Figure 1C, 1D).…”
Section: Figure 1b)supporting
confidence: 92%
“…We also detected low to mid-levels of E5 in the pancreases of immunocompetent hFcRn Tg32 mice (5 of 5 mice) and to a much lesser extent in liver (1 of 5 mice) (Supplemental Figure 1C, 1D). There was no detectable virus in any animals expressing the murine homologue of FcRn (Supplemental Figure 1C, 1D), consistent with our previous work (21). Collectively, these data show that echovirus infections in the brain require expression of hFcRn and that the primary barrier to infection is type I IFN-mediated signaling.…”
Section: Figure 1b)supporting
confidence: 89%
See 3 more Smart Citations